2011
DOI: 10.5194/hess-15-3577-2011
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of land emissivity estimates from AMSR-E at C and X bands to surface properties

Abstract: Abstract. Microwave observations at low frequencies exhibit more sensitivity to surface and subsurface properties with little interference from the atmosphere. The objective of this study is to develop a global land emissivity product using passive microwave observations from the Advanced Microwave Scanning Radiometer -Earth Observing System (AMSR-E) and to investigate its sensitivity to land surface properties. The developed product complements existing land emissivity products from SSM/I and AMSU by adding l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…High emissivity-based MPDI values greater than 0.06 are found for low soil moisture and low NDVI values in all products. This is in line with previous studies that suggest that the contrast between horizontal and vertical microwave signals is higher in desert regions with almost no vegetation (e.g., Norouzi et al, 2011;Prigent et al, 2006). Soil moisture has been found to decrease the emissivity across the frequencies (Basist et al, 1998).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…High emissivity-based MPDI values greater than 0.06 are found for low soil moisture and low NDVI values in all products. This is in line with previous studies that suggest that the contrast between horizontal and vertical microwave signals is higher in desert regions with almost no vegetation (e.g., Norouzi et al, 2011;Prigent et al, 2006). Soil moisture has been found to decrease the emissivity across the frequencies (Basist et al, 1998).…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have shown that differences in channel frequencies and incidence angles between AMSR-E and SSMI/I channels may lead to around 0.01 error in the emissivity retrieval (Norouzi et al, 2011). TMI and SSM/I have similar emissivity values especially at 10, 19, and 37 GHz.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations